PENGARUH KEPUASAN GAJI, PENGEMBANGAN KARYAWAN DAN DUKUNGAN ORGANISASIONAL TERHADAP TURNOVER INTENTION (Studi pada Karyawan PT Asuransi Tokio Marine Indonesia) - Andalen, Abram; Darmastuti, Ismi (Faculty of Economics and Business Diponegoro University, 2015)
Turnover intention is the desire or intention of employees to qui from his job voluntarily according to their own choice. Turnover intention may be the first indication of employees who leave a job that can lead to high levels of employee turnover. organizations need to reduce it to an acceptable level. In order to manage the human resources, organizations have to pay attention to the pay satisfaction, provide organizational support, and help employees in their development.This research aims to analyze the effect of salary satisfaction, employee development and organizational support on turnover intention. Data was collected by using a questionnaire. Population of this research are employees of PT Asuransi Tokio Marine Indonesia, using 77 employees as respondents.The analysis technique used is multiple linear regression. Result finds that pay satisfaction, employee development and organizational support negatively affect turnover intention.